2016
DOI: 10.1097/moo.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

The sinonasal bacterial microbiome in health and disease

Abstract: Purpose of review The development of culture-independent bacterial DNA sequencing techniques and integration into research practice has led to a burgeoning interest in the microbiome and its relevance to human health and disease. Introduction into the study of chronic rhinosinusitis in the past few years has shaped current thinking on the role of bacteria in the disease process. Recent findings Rich and diverse populations of bacteria inhabit the sinonasal cavity at all times. Decreased bacterial richness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 46 publications
1
58
0
4
Order By: Relevance
“…Within the sinuses, a similar mucosal bacterial burden is present regardless of the presence or severity of sinus disease, suggesting a confluent bacterial community may saturate mucosal surfaces in both diseased and healthy sinuses . Although mucosal bacteria are similar in number across disease states, community composition varies greatly …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the sinuses, a similar mucosal bacterial burden is present regardless of the presence or severity of sinus disease, suggesting a confluent bacterial community may saturate mucosal surfaces in both diseased and healthy sinuses . Although mucosal bacteria are similar in number across disease states, community composition varies greatly …”
Section: Discussionmentioning
confidence: 99%
“…7 Although mucosal bacteria are similar in number across disease states, community composition varies greatly. [5][6][7]36 There is a growing body of literature identifying the importance of sinus microbes in the pathogenesis of CF pulmonary disease. Culture studies have demonstrated concordance between sinus and pulmonary pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…A major implication of the current study is the potential moving forward for a single-site sampling method, an identified need to facilitate future longitudinal studies [50]. At this point, analyses of sinus microbiota have been challenging and difficult to replicate due to concerns about inclusion of control subjects, optimal sampling technique, sampling site, laboratory protocols, and data analysis pipelines [51].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these few studies claim that CRS patients can have a reduced diversity, altered nasal microbiota, an increase in S. aureus or Corynebacterium tuberculostearicum abundance, and greater densities of bacterial and/or fungal cells. However, the role of bacteria in the pathogenesis of CRS has yet to be established with certainty, as recent reviews argue that there is still no consensus on the most common bacteria present in the healthy or diseased state, and there is no clear causative or protective single organism (Mahdavinia et al, 2016;Ramakrishnan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%